Moving from health education to health promotion: Developing the health education curriculum in Cyprus - Ioannou, Soula; Charalambous, Neofytos; Kouta, Christiana (My University, 2012)
Purpose: This paper seeks to discuss the rationale of the newly reformed health education curriculum in Cyprus, which aspires to enable not only teachers, but also all the school personnel, to work from the perspective of health promotion. It is a curriculum which moves from the traditional approach of health education focusing on individual lifestyle/behaviour modification into approaches that recognise and tackle the determinants of health. Design/methodology/approach: The paper critically discusses the structure and the content of the learning objectives of this curriculum that encourages teachers to work in a health promoting way. Findings: The central goal of this curriculum is to enable students and schools to act as health agents, addressing the structural determinants of health and promoting environmental changes. The optimum level for all topics of the curriculum is achieved through learning objectives, which concern three interconnected levels. These are: investigating determinants of health, practising action competency skills for health and achieving changes in favour of health. All levels are means as well as end products in terms of the curriculum objectives. Practical implications: The outcome of the development of the health education curriculum acts as a guide for school interventions, through a methodological framework, which encourages participants to identify and promote environmental changes that facilitate healthy choices. This is of significance to those working in the field of health promotion and who seek to establish a new language of health promotion that goes beyond the pervasive discourse of individual lifestyles. Social implications: The implementation of the particular health education curriculum will promote not only health in the school community but also in the local community. This is because a key principle which underlies the curriculum is the involvement of the students, school staff, family and community in everyday health promotion practice. It also promotes the development of partnerships among them. Originality/value: This is an innovative curriculum for Cyprus, based on health promotion and health education principles, but at the same time taking in account the local socio-cultural and political perspective. This curriculum may be applicable to other European countries.
Keywords: Health education; Health promotion; Curriculum